جی ایس داراکی کتاب ’’رسول عربیؐ ‘‘ کاتجزیاتی مطالعہ (Al-Qamar, 2024)
Biography refers to describing the events of the Holy Prophet's life, his style of life and teachings. In every era, biographers wrote books on the life of the Holy Prophet. Biography began in early Islam. The appearance of those who picked up the pen on the subject of biography took place during the Prophet’s (peace and blessings of Allah be upon him) biographers began to write in honor of him. This trend started in the subcontinent as well Apart from Muslim biographers in the subcontinent, non-Muslim biographers also entered this field.  Among these biographers, two types of biographers emerged, one class was the one who was inspired by the teachings of the Holy Prophet (peace be upon him) and wrote out of love for the Prophet (peace be upon him) and the other class was the one who wrote against the Holy Prophet (peace be upon him) out of hatred for the Prophet (peace be upon him) due to jealousy.  In such a situation, some non-Muslim biographers wrote moderately. Yes, I am. S. Dara is counted among the authentic biographers. He supported realism and in honor of him, he wrote in such a way that even Muslim biographers could not help but praise him. When a Muslim biographer writes on this subject, it is generally believed that he as a believer has given a positive account of the life of his beloved Prophet. But when a non-Muslim steps into this valley, a series of questions begin to arise. People start thinking that why did he, as a non-Muslim, write on the biography of the Messenger of Allah? Does his writing contain the fragrance of the Prophet's love or the poison of the Prophet's hatred?
Keywords: Holy Prophet's life; Orientalists; Muslim biographer; non-Muslim steps